Human Response and Annoyance Towards Ground-Borne Vibration Induced by Railway Traffic - Mohd Lazi, Mohd Khairul Afzan; Adnan, Muhammad Akram; Adnan, Muhammad Akram (International Journal of Integrated Engineering, 2022)
Limited findings regarding the level of perceived irritability and annoyance experienced by the affected people living near to the source of the vibrations especially in Malaysia became the motivation for this study. This paper attempted to gather the empirical data by setting up a few basic instruments to measure the vibration induced by railway traffic at the site under study. The collected data would determine the vibration level and how it affects human annoyance based on the Malaysian standard guideline. In this paper, identifying the vibration level induced by rail traffic will determine the level of annoyance and discomfort experienced by the residents living close to the railway tracks. This data can be used to mitigate the problems created by the ground-borne vibration in Malaysia. The vibration data were observed to investigate the level of vibration towards the human response and annoyance by comparing the collected data to the standard guidelines. In this study, the receivers of the vibrations were limited to the residents living nearby the railway track along with the designated areas under study. This paper is expected to bridge the gap of knowledge regarding the fundamental understanding of the ground-borne vibration that consists of the combination of several branches of learning on the local rail traffic condition.